Law No. 176 of the year 2022 Amending Certain Provisions of the Uniform Tax Procedure Law Promulgated By Law No. 206 of the Year 2020 = قانون رقم 176 لسنة 2022 بتعديل بعض أحكام قانون الإجراءات الضريبية الموحد الصادر بالقانون رقم 206 لسنة 2020 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic